The effectiveness of integrated marketing communication used by Syarikat Takaful Malaysia Berhad / Balqis Hafizah Idris - Idris, Balqis Hafizah (Faculty of Business and Management, 2006)
The main objective of this research was to explore whether STMB is implementing the right strategies in promoting their brand and to determine if IMC plays an important role in strengthening the STMB market position. The respondents of this study were general Malaysian who lives in Klang Valley and are exposed to various media. Seventy two questionnaires had been distributed in Klang Valley areas. The researcher had used judgmental sampling as the sampling technique. The questionnaire was designed to the selected respondents which they were asked varieties of questions regarding their opinion, knowledge and perception towards STMB. The process of analyzing and interpreting data has been presented with tables using methods such as frequency distribution, descriptive analysis and cross tabulation. The research shows that Takaful Malaysia is still unable to fully maximize their integrated marketing communication in creating effective communication throughout their establishment in 21 years of involvement in the takaful industry.